Kyrgyz Republic : 2013 Article IV Consultation and Fourth Review Under the Three-Year Arrangement Under the Extended Credit Facility, Request for Waiver of Nonobservance of a Performance Criterion, and Request for Modification of Performance Criteria-Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Kyrgyz Republic. (IMF Staff Country Reports; Country Report ;, 2013)
The shift to a parliamentary democracy in 2010 provided an impetus for the Kyrgyz Republic to reform the economy. Despite the recent progress, the Kyrgyz Republic faces significant economic challenges, which will require actions on many fronts. Improving the business climate, governance, and institutions remains a key pillar of sustainable and inclusive growth. Restoring fiscal sustainability will be essential, as the budget has become more dependent on external assistance since the 2009 global and 2010 domestic crises. Tight monetary policy continues to be warranted to keep inflation at bay.